2022
DOI: 10.1177/15593258221105370
|View full text |Cite
|
Sign up to set email alerts
|

Baricitinib is Effective in Treating Progressing Vitiligo in vivo and in vitro

Abstract: Objective To evaluate the clinical efficacy and safety of baricitinib, a Janus kinase (JAK) inhibitor, in treating patient with progressing vitiligo, and to further explore the regulation of baricitinib on melanocytes (MCs) in vitro. Methods Four patients with progressing vitiligo were treated with oral baricitinib for a total of 12 weeks. MCs were cultured in vitro and irradiated by high-dose ultraviolet B (UVB, 150mJ/cm2) to make an MC damaged model (MC-Ds). Baricitinib was added at a final concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Several studies have shown that baricitinib is effective in treating various skin conditions such as atopic dermatitis (AD), alopecia areata (AA), psoriasis, and vitiligo 55 . The results of our study have also shown the significant effectiveness of this drug in treating vitiligo 56 …”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Several studies have shown that baricitinib is effective in treating various skin conditions such as atopic dermatitis (AD), alopecia areata (AA), psoriasis, and vitiligo 55 . The results of our study have also shown the significant effectiveness of this drug in treating vitiligo 56 …”
Section: Discussionsupporting
confidence: 65%
“…A total of 12 patients participated in these studies. The first study demonstrated that baricitinib was both effective and safe in treating progressing vitiligo (with a significance level of p < 0.05) 35 . In a study involving eight vitiligo patients, baricitinib was administered and their progress was monitored at 3 and 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective study, Liu et al 7 reported that skin exposure to ultraviolet light appears to be required to achieve repigmentation using JAK inhibitors as evidenced by increased JAK1 levels in vitiligo patients that were downregulated after NBUVB treatment. 8 Recently, Dong et al 10 found that in vitro baricitinib could promote tyrosinase activity, melanin content and tyrosinase, tyrosinase-related protein-1 gene expression of melanocytes damaged model, which will be contributed to repigmentation of vitiligo.…”
Section: Discussionmentioning
confidence: 99%